"Nobody is perfect": Asset pricing and long-run survival when heterogeneous investors exhibit different kinds of filtering errors - Nicole Branger; Christian Schlag; Lue Wu (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
In this paper we analyze an economy with two heterogeneous investors who both exhibit misspecified filtering models for the unobservable expected growth rate of the aggregated dividend. A key result of our analysis with respect to long-run investor survival is that there are degrees of model misspecification on the part of one investor for which there is no compensation by the other investor's deficiency. The main finding with respect to the asset pricing properties of our model is that the two dimensions of asset pricing and survival are basically independent. In scenarios when the investors are more similar with respect to their expected consumption shares, return volatilities can nevertheless be higher than in cases when they are very different.
urn:nbn:de:hebis:30:3-386381
Keywords: G11; G12; 330; General Equilibrium; Asset Allocation; Learning; Different Beliefs; Over-Confidence